2018
DOI: 10.1074/jbc.ra118.002800
|View full text |Cite
|
Sign up to set email alerts
|

mTOR complex 1 controls the nuclear localization and function of glycogen synthase kinase 3β

Abstract: Glycogen synthase kinase 3β (GSK3β) phosphorylates and thereby regulates a wide range of protein substrates involved in diverse cellular functions. Some GSK3β substrates, such as c-Myc and Snail, are nuclear transcription factors, suggesting the possibility that GSK3β function is controlled through its nuclear localization. Here, using ARPE-19 and MDA-MB-231 human cell lines, we found that inhibition of mTOR complex 1 (mTORC1) leads to partial redistribution of GSK3β from the cytosol to the nucleus and to a GS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(100 citation statements)
references
References 83 publications
2
84
0
1
Order By: Relevance
“…DHHC5 localizes at the postsynaptic membrane of neurons through phosphorylation of Y533 in a manner regulated by Fyn 35 . To test the possible regulation of DHHC5 by Fyn and/or phosphorylation upon USMB treatment, we first examined the phosphorylation of DHHC5 using phos-tag gel electrophoresis, a method that exaggerates the apparent molecular weight differences elicited by protein phosphorylation 52 . We observed that USMB and USMB+desipramine elicited a reduction in the apparent molecular weight of These results indicate that USMB treatment leads to a reduction of DHHC5 phosphorylation, and that this phenomenon is controlled by Fyn.…”
Section: Enhanced Flotillin-dependent Fluid-phase Uptake Induced By Umentioning
confidence: 99%
See 4 more Smart Citations
“…DHHC5 localizes at the postsynaptic membrane of neurons through phosphorylation of Y533 in a manner regulated by Fyn 35 . To test the possible regulation of DHHC5 by Fyn and/or phosphorylation upon USMB treatment, we first examined the phosphorylation of DHHC5 using phos-tag gel electrophoresis, a method that exaggerates the apparent molecular weight differences elicited by protein phosphorylation 52 . We observed that USMB and USMB+desipramine elicited a reduction in the apparent molecular weight of These results indicate that USMB treatment leads to a reduction of DHHC5 phosphorylation, and that this phenomenon is controlled by Fyn.…”
Section: Enhanced Flotillin-dependent Fluid-phase Uptake Induced By Umentioning
confidence: 99%
“…Endogenous flotillin-1 or -2, DHHC5 or γH2AX were labelled by performing indirect immunofluorescence as previously described 52 . Samples were fixed in a solution of 4% PFA and permeabilized by Triton-X100 (for flotillin labeling experiments) or ice-cold methanol (for DHHC5 labeling experiments).…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
See 3 more Smart Citations